Pengembangan Aplikasi Monitoring dan Kontrol untuk Greenhouse Hidroponik - Muhammad Aji; Husni Thamrin (Jurnal Ilmiah Informatika, 2025)
This research aims to develop an Internet of Things (IoT) based monitoring and control application for hydroponic greenhouses using the Nutrient Film Technique (NFT) method for lettuce (Lactuca sativa L.). Hydroponics has emerged as an efficient solution for agricultural production in limited spaces, but environmental management challenges often remain a primary obstacle. The application is designed to automatically monitor and control environmental conditions, such as temperature, solution pH, and nutrient concentration, to reduce the risk of bolting that can diminish harvest quality. Software development was conducted using the Scrum methodology, which supports iterative and adaptive processes, employing Model-View-ViewModel (MVVM) architecture and clean architecture to create a modular and easily maintainable code structure. Jetpack Compose was utilized to generate a responsive and efficient user interface. Research findings demonstrate that the application offers key features including real-time monitoring through MQTT protocol, manual and automatic control, data history visualization in graphs, weather prediction, and hydroponic guidance. Application validation using the Aiken index showed a very high validity level (> 0.80), while black box testing ensured that all application functions operated by user requirements. This research is expected to improve hydroponic greenhouse management efficiency and significantly contribute to IoT technology development in the agricultural sector.